(untitled) (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
This study aims at scrutinizing the hadith of Habiba bt. Sahl al-Ansariyya as recorded in classical hadith collections through an analysis of the circumstances that has surrounded the incident. This study employs inductive, comparative as well as content analysis methodology to highlight the prophetic wisdom and his approach in dealing with the marriage problems. The diversification of prophetic approaches related to emotional aspect or religious and health aspects are admirable and give insight for solving the marital issues. Overall, the findings from this qualitative study of Habiba’s hadith highlighted that the hadith is authentic and was the first practical application of the khul’ (a woman can divorce her husband) but the hadith shall not be considered as the asbab al-nuzul (circumstances of revelation). Later, this hadith is accepted as a general legislation in the Muslim world. The hadith also provides a proof of legitimacy for the husband to request khul’ from his wife in the event of nushuz (disobedience). However, the legitimacy is subject to condition with restrain of seizing the wealth of her wife. This study also recommends a serious thought in the application of khul’ in order to preserve the family institution from disruption and destruction.